Studi Kelayakan Lokasi Budidaya Rumput Laut di Perairan Kampung Menyumfoka dan Pulau Kaki Kabupaten Manokwari - Bayu Pranata; Syafrudin Raharjo; Marhan Manaf; Ida Lapadi; Anjeli Paisey (Fakultas Perikanan dan Ilmu Kelautan, Universitas Papua, 2022)
The feasibility study of the location of seaweed cultivation is very important to be carried out in order to ensure the sustainability of the cultivation activities in question. Therefore, this study aims to examine the feasibility of the technical aspects of seaweed cultivation to support the development of seaweed cultivation in the coastal waters of Mengumfoka Village and Kaki Island, Manokwari Regency. The research method is the observation method with survey techniques (in situ and ex situ). The results showed that the two research sites had characteristics of the physical-chemical and biological conditions of the waters that could support seaweed cultivation activities. Location KA1 has a score of 86.2, which means the location is highly suitable, while location KA2 has a score of 75.4 or moderately suitable as a location for seaweed cultivation. In general, KA1 and KA2 locations have the same conditions, but KA2 locations are more open than KA1 locations, so that KA2 locations have more risk due to large currents and waves due to seasons. So the location of KA2 can only do seaweed cultivation during the shady season.